Effect-directed analysis for revealing aryl hydrocarbon receptor agonists in sediment samples from an electronic waste recycling town in China. (1st September 2022) - Ma, Qianchi; Liu, Yanna; Yang, Xiaoxi; Guo, Yunhe; Xiang, Tongtong; Wang, Yi; Yan, Yuhao; Li, Danyang; Nie, Tong; Li, Zikang; Qu, Guangbo; Jiang, Guibin
Abstract: Exposure to electronic and electrical waste (e-waste) has been related to a few adverse health effects. In this study, sediment samples from an e-waste recycling town in China were collected, and aryl hydrocarbon receptor (AhR) agonists in the samples were identified using an effect-directed analysis (EDA) strategy. The CBG2.8D cell line reporter gene bioassay was used as a toxicity test, while suspect screening against chemical databases was performed for potential AhR agonist identification where both gas chromatography- and liquid chromatography-high resolution mass spectrometry analyses were run. When the original sample extract showed high AhR-mediated activity, sample fractionation was performed, and fractions exhibiting high bioactivity were chemically analyzed again to reveal the corresponding AhR agonists. In total, 23 AhR agonists were identified, including 14 commonly known ones and 9 new ones. Benzo [ k ]fluoranthene and 6-nitrochrysene were the dominant AhR agonists, covering 16–71% and 2.7–12%, respectively, of the AhR activation effects measured in the parent extracts. The newly identified AhR-active chemicals combined explained 0.13–0.20% of the parent extracts' effects, with 7, 12-dimethylbenz [ a ]anthracene and 8, 9, 11-trimethylbenz [ a ]anthracene being the major contributors. A diagnostic isomer ratio analysis of polycyclic aromatic hydrocarbons suggested that the major source of AhR agonists identified in these e-waste related sediment samples were probably petroleum product combustion and biomass combustion. In the future, for a more comprehensive AhR agonist investigation, in-house chemical synthesis and purification, and, when necessary, a secondary sample fractionation, would be beneficial. Graphical abstract: Image 1 Highlights: The EDA strategy was used to identify AhR agonists in e-waste related sediments. Both GC- and LC-QExactive instruments were used to systemically identify AhR agonists. The 23 identified chemicals explained 27–94% of the samples' AhR-mediated activity.